Prognostic criteria for the development of infective endocarditis in children with heart pathology - Porokhnya N.G. (Medičnì Perspektivi)
To determine the most informative prognostic signs of infectious endocarditis development in children with heart pathology on the background of bacterial infections clinical course of 15 cases of infective endocarditis in children aged from 1 month to 17 years was performed. The comparison group consisted of 40 children aged 5 - 17 years with mitral valve prolapse. Of 19 analyzed clinical-anamnestic predictive diagnostic features for the development of infective endocarditis in children, presence of febrile fever during infusion therapy, the operated congenital heart disease, treatment in an intensive therapy unit with mechanical ventilation, intravenous infusions through a catheter lasting more than three days, a positive blood culture during the disease course, diagnostic catheterization of large vessels were of high informative value. In a positive prognosis of infective endocarditis development with a probability of 95% and more, children underwent complex of therapeutic measures with the following observation of pediatric cardio-rheumatologist.